Carthamus tinctorius L. Inhibits Proliferation of Lung Cancer A549 Cells and Tender’s Mitochondrial Protection - Dailah, Hamad Ghaleb (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Plant-based products are well-known as long-lasting chemo preventive and chemotherapeutic medicines against cancer. Objectives: The purpose of this research is to identify out how safflower extract affects A549 cells. Materials and Methods: The antiproliferative activity was determined using the Trypan blue assay, while the cytotoxicity was determined using the MTT assay. The ethidium bromide/acridine orange (AO/EB) dual staining method was used to observe the apoptotic inducing effect and the morphological assessment of A549 cells using phase contrast microscopy was studied to discern the nuclear changes if any on treatment with safflower. The mitochondrial membrane potential was studied using a cationic lipophilic dye rhodamine 123 under a confocal microscope, and oxidative stress was assessed using 2’,7’-dichlorodihydrofluorescein diacetate (DCFH-DA) labelling. Results: The trypan blue assay speculated that there was a decrease in cell viability at highest concentration and that the effect was dose dependent. The MTT assay revealed that cytotoxicity increases in cells treated with higher concentration. The LC50 range of the sample was found at 250 μg/ml concentration at 52.2%, whereas the viability of the cell declined to 28.19% at 350μg/ml concentration. The morphological features like shrinkage, detachment, membrane blebbing, and distorted shape were observed on safflower treated A549 cells that supports the antiproliferative activity. The ethidium bromide and acridine orange staining substantiates that safflower extract induces apoptosis wherein the untreated A549 cells showed green fluorescence with intact nuclear morphology and cells treated with safflower extract (200 μg and 250 μg/ml), showed apoptotic bodies, clearly validating the apoptosis inducing effect by safflower on A549 cells. Also, the safflower extract protects the mitochondria by decreasing the oxidative stress and by altering the mitochondrial membrane potential. Conclusion: Thus, it is found that safflower extract exerts its antiproliferative activity by inducing apoptosis and protects mitochondria by combating oxidative stress.
Keywords: Safflower; Oxidative stress; Cytotoxicity; Mitochondria; Apoptosis